Food-cue affected motor response inhibition and self-reported dieting success: a pictorial affective shifting task - Meule, Adrian; Lutz, Annika P.; Krawietz, Vera; Stützer, Judith; Vögele, Claus; Kübler, Andrea (Frontiers in Psychology, 2014)
Behavioral inhibition is one of the basic facets of executive functioning and is closely related to self-regulation. Impulsive reactions, i.e. low inhibitory control, have been associated with higher body-mass-index (BMI), binge eating, and other problem behaviors (e.g. substance abuse, pathological gambling, etc.). Nevertheless, studies which investigated the direct influence of food-cues on behavioral inhibition have been fairly inconsistent. In the current studies, we investigated food-cue affected behavioral inhibition in young women. For this purpose, we used a go/no-go task with pictorial food and neutral stimuli in which stimulus-response mapping is reversed after every other block (affective shifting task). In study 1, hungry participants showed faster reaction times to and omitted fewer food than neutral targets. Low dieting success and higher BMI were associated with behavioral disinhibition in food relative to neutral blocks. In study 2, both hungry and satiated individuals were investigated. Satiation did not influence overall task performance, but modulated associations of task performance with dieting success and self-reported impulsivity. When satiated, increased food craving during the task was associated with low dieting success, possibly indicating a preload-disinhibition effect following food intake. Food-cues elicited automatic action and approach tendencies regardless of dieting success, self-reported impulsivity, or current hunger levels. Yet, associations between dieting success, impulsivity, and behavioral food-cue responses were modulated by hunger and satiation. Future research investigating clinical samples and including other salient non-food stimuli as control category is warranted.